Periconceptional changes in thyroid function: a longitudinal study - Balthazar Ursula; Steiner Anne Z (BMC, 2012)
Abstract Background Limitations in our current knowledge of normative physiologic changes in thyroid function during the periconception window narrow our ability to establish an optimal approach to screening and diagnosis of thyroid disease in pregnant women. The objective of this study was to characterize changes in thyroid function during the transition from the pre-pregnant to pregnant state in normal fertile women. Methods Women (N = 60) ages 30-42 years without a history of thyroid disease, who were planning pregnancy, were observed prospectively before and during early pregnancy. Thyroid function (thyroid stimulating hormone, TSH and free thyroxine, FT4) was measured before conception and between 6 and 9 weeks gestation. Pre-pregnancy samples were analyzed for thyroid antibodies. Bivariate analyses and longitudinal curves (general estimating equation models) were used to analyze changes in thyroid function during the periconception window by antibody status. Results Pre-pregnancy TSH values were significantly higher than early pregnancy TSH (p < 0.001), but FT4 values did not differ (p = 0.53). TSH declined as gestational age increased (P < 0.01). Thyroid antibody positive women had a higher pre-pregnancy TSH compared to antibody negative women (p < 0.01). Periconceptional change in thyroid function was more variable among women with antibodies (p < 0.001). 50% of women with elevated pre-pregnancy TSH values (TSH > 3.0 mIU/L) had normal TSH values (TSH < 2.5 mIU/L) in pregnancy. Conclusions TSH values decline during the transition from pre-pregnancy to early pregnancy. The change in TSH appears to be less predictable in women with thyroid antibodies. Periconceptional changes in thyroid function should be considered in formulating prenatal thyroid screening guidelines.